2021
DOI: 10.3390/en14217337
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Aspects of Electric Energy Storage in a Mine Shaft—Budryk Case Study

Abstract: The transformation of the energy sector towards an increased share of renewable energy sources in the energy mix requires attention in the area of electricity storage. Renewable energy sources (photovoltaics or wind energy) are marked by the intermittency of electricity production and require the construction of energy storage to adapt the energy supply to the demand, providing greater stability. The authors focused on verifying the solution of gravitational energy storage in existing shafts of hard coal mines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…There are works that consider the use of gravitational energy storage systems with the integration of renewable energy sources [16,17]. The authors of [18] analyzed the prospect of using of a gravitational energy storage system in existing shafts of hard coal mines in Poland. The authors found that the obtained economic effects of the solution were low, and therefore there was no economic justification for activities related to its implementation.…”
Section: Methods For Electric Energy Accumulationmentioning
confidence: 99%
“…There are works that consider the use of gravitational energy storage systems with the integration of renewable energy sources [16,17]. The authors of [18] analyzed the prospect of using of a gravitational energy storage system in existing shafts of hard coal mines in Poland. The authors found that the obtained economic effects of the solution were low, and therefore there was no economic justification for activities related to its implementation.…”
Section: Methods For Electric Energy Accumulationmentioning
confidence: 99%
“…With regard to medium-sized and large industrial enterprises, integration into the European energy system has provoked increased demands for non-alternative green generation from alternative energy sources. Moreover, there is even a lot of research conducted on greener energy solutions for companies based on conventional sources of energy, for example: (Kulpa et al 2021;Dyczko et al 2021;Stecuła and Brodny 2018;Stecuła 2018). The effective integration of energy facilities into the energy markets of Ukraine is presented to ensure the stabilization of network operating parameters as well as allowing the saving and utilization of industrial waste in Ukrainian enterprises and stabilizing tariffs for the entire range of energy-consumption stakeholders.…”
Section: Smart-chain Of Energy Decentralization In Ukrainementioning
confidence: 99%
“…(2) pumped storage power plants: problems related to building (flooding of territories, capital investments) [23,24]; (3) low efficiency, limited capabilities, or low availability of technology-hydrogen storage technologies, condenser batteries, mechanical accumulators, compressed air storage, gravity storage, etc., [23,25,26].…”
Section: Introductionmentioning
confidence: 99%